Number fluctuations of cold, spatially split bosonic objects - Sakmann, Kaspar; Streltsov, Alexej Iwanowitsch; Alon, Ofir E.; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2011)
We investigate the number fluctuations of spatially split many-boson systems employing a theorem about the maximally and minimally attainable variances of an observable. The number fluctuations of many-boson systems are given for different numbers of lattice sites and both mean-field and many-body wave functions. It is shown which states maximize the particle number fluctuations, both in lattices and double wells. The fragmentation of the states is discussed, and it is shown that the number fluctuations of some fragmented states are identical to those of fully condensed states.